P5.041 TB Treatment For HIV Positive Pregnant Women: Challenges to Screening and Diagnosis. (13th July 2013) - Plessis, E du; Shaw, S Y; Gichuhi, M; Kimani, J; Gelmon, L; Gelmon, L; Avery, L S
Abstract : Background: According to Kenya's PMTCT guidelines, all HIV positive women who present for antenatal care should be tested for TB. Methods: HIV-positive, pregnant women were recruited from two maternity hospitals in Nairobi, Kenya. The results presented here are based on surveys completed at baseline as well as 48 hour follow up. This data was collected from 505 women as part of a study on the use of mobile technology in PMTCT programmes. Questionnaires included questions on socio-economic characteristics, history of current and previous pregnancies, knowledge of PMTCT, TB screening and treatment and the use of Nevirapine. Chi-square tests and multivariable logistic regression were used to assess statistically significant associations between variables of interest and TB screening. Results: Overall screening for TB in our sample was 10.3% with no significant difference between the two hospitals (11.4% versus 8.4%). Analysis also revealed no significant difference between groups based on sociodemographic status (including age, education, marital status and income) or based on the number of antenatal visits or gestational age at first presentation. Conclusion: Reportedly, 80% of TB patients are given access to HIV testing and a further 27% of those who test pest positive are placed on ART. TB screening for pregnant women seem to be offered less regularly, however, with only 10% of women screened. In our sample, the lack of significant difference in screening between facility, by sociodemographic characteristics or by when they access services seems to suggest suboptimal TB screening in pregnant women is a systemic issue.